Realizing Climate-Resilient MSMEs through Sustainable Accounting - Cici girikallo; Maya Sari Rupang (AIBPM Publisher, 2026)
This study examines the level of understanding and awareness of climate change risks among agricultural Micro, Small, and Medium Enterprises (MSMEs) in Merauke Regency, South Papua, and its implications for sustainable accounting practices. A qualitative approach was employed through interviews, observation, and documentation involving 12 agricultural MSMEs in Semangga, Tanah Miring, and Kurik Districts. The findings show that MSME actors have experienced the impacts of climate change, such as floods, droughts, and uncertain seasonal patterns; however, their understanding remains limited and has not been integrated into financial management practices. Most MSMEs still use simple bookkeeping and do not record climate-related losses as business risks. Despite these limitations, MSMEs demonstrate adaptive strategies through planting adjustments, commodity diversification, and social cooperation. This study contributes by highlighting the importance of climate risk awareness and sustainable accounting practices to strengthen the resilience of agricultural MSMEs in vulnerable rural areas.